Graham Richardson and the doctors - O'Neill, Ward, 1951- (1995)
Cartoon drawing of Graham Richardson trying to revive an overweight doctor.
Condition: good.
File no: 204/16/23
Inscriptions: signed "O'Neill"-- l.l. corner. "Graham Richardson & the doctors" -- in pencil bot. c. "Tom Burton - Canberra observed" -- lower c.
Part of: Ward O'Neill collection.
Also available online
Keywords: Richardson, Graham, -- 1949- -- Caricatures and cartoons; Politicians -- Australia -- Caricatures and cartoons; Australia -- Politics and government -- 1990-2001 -- Caricatures and cartoons